Principles of ocean physics - Apel, John R. (International geophysics series, 1988)
In recent years, significant advances in both the theoretical and observational sides of physical oceanography have allowed the ocean's physical behavior to be described more quantitatively. This book discusses the physical mechanisms and processes of the sea, and will be valuable not only to oceanographers but also physicists, graduate students, and scientists working in dynamics or optics of the marine environment.